From lows to highs: using low‐resolution models to phase X‐ray data. (5th November 2013) - Stuart, David I.; Abrescia, Nicola G. A.
Abstract : The study of virus structures has contributed to methodological advances in structural biology that are generally applicable (molecular replacement and noncrystallographic symmetry are just two of the best known examples). Moreover, structural virology has been instrumental in forging the more general concept of exploiting phase information derived from multiple structural techniques. This hybridization of structural methods, primarily electron microscopy (EM) and X‐ray crystallography, but also small‐angle X‐ray scattering (SAXS) and nuclear magnetic resonance (NMR) spectroscopy, is central to integrative structural biology. Here, the interplay of X‐ray crystallography and EM is illustrated through the example of the structural determination of the marine lipid‐containing bacteriophage PM2. Molecular replacement starting from an ∼13 Å cryo‐EM reconstruction, followed by cycling density averaging, phase extension and solvent flattening, gave the X‐ray structure of the intact virus at 7 Å resolution This in turn served as a bridge to phase, to 2.5 Å resolution, data from twinned crystals of the major coat protein (P2), ultimately yielding a quasi‐atomic model of the particle, which provided significant insights into virus evolution and viral membrane biogenesis.